Splenic macrophage functional profile and its role in the immunopathogenesis of canine visceral leishmaniasis - de Souza, Tainã Luís; Santiago, Marta de Almeida; Ribeiro, Francini Neves; Figueiredo, Fabiano Borges; Junior, Artur Augusto Velho Mendes; Menezes, Rodrigo Caldas; Porrozzi, Renato; Morgado, Fernanda Nazaré (Frontiers in Immunology, 2025)
IntroductionVisceral leishmaniasis (VL) represents a major public health challenge, with the spleen frequently identified as one of the primary target organs. Dogs recognized as urban reservoir hosts, commonly harbor chronic infections characterized by elevated parasite burdens across multiple tissues. This study aims to analyze functional markers of M1 and M2 responses, as well as PD-L1+ macrophages in the spleens of naturally infected dogs with Leishmania infantum, and to correlate these findings with splenic white pulp disorganization, parasitic load, and clinical severity.MethodsThirty-four VL-infected dogs were enrolled, each undergoing clinical evaluation to determine a clinical severity score. Histopathological analyses were performed to evaluate splenic white pulp disorganization, while quantitative PCR and immunohistochemistry were employed to assess parasite burden. Immunological markers were analyzed via immunohistochemistry, immunofluorescence, and flow cytometry.ResultsSplenic white pulp disorganization was observed in most animals, indicating marked tissue disruption. Immunostaining demonstrated the presence of NOS2+, Arginase 1+, pSTAT3+, CD206+, and TGF-β+ cells, reflecting the engagement of both M1 and M2 macrophage subsets in the immune response, with a predominance of M1 profile. Elevated CD206 expression correlated with splenic white pulp disruption and parasite load. A notable finding was the decrease in the CD68+NOS2+/CD68+Arginase-1+ ratio in animals with higher parasite load. Additionally, significant PD-L1 expression was detected in macrophages within spleens exhibiting splenic white pulp disorganization, indicative of a pro-exhaustion cellular phenotype. Flow cytometry analysis identified co-expression of arginase-1 and PD-L1, as well as Arginase-1high+ cells. Finally, arginase-1high+ cells directly correlated with arginase-CD14-PD-L1+ cells suggesting that not only macrophages, but others arginase-1high expressing cell types may contribute for suppressive/regulatory profile during the immunopathogenesis of canine VL.ConclusionThe persistent presence of CD206, CD68+Arginase-1+ and CD68+PD-L1+ cells within the inflamed, parasitized splenic tissue, alongside a relative decline in CD68+NOS2+ cells, may create a permissive environment for parasite survival and replication, thereby sustaining the inflammatory response. This chronic exposure to antigenic and inflammatory stimuli likely contributes to persistent tissue damage, exemplified by splenic white pulp disorganization in the spleen, and exacerbates disease progression.